Role of Jagged1-mediated Notch Signaling Activation in the Differentiation and Stratification of the Human Limbal Epithelium - González, Sheyla (Cells, 2020)
The Notch signaling pathway plays a key role in proliferation and differentiation. We investigated the effect of Jagged 1 (Jag1)-mediated Notch signaling activation in the human limbal stem/progenitor cell (LSC) population and the stratification of the limbal epithelium in vitro. After Notch signaling activation, there was a reduction in the amount of the stem/progenitor cell population, epithelial stratification, and expression of proliferation markers. There was also an increase of the corneal epithelial differentiation. In the presence of Jag1, asymmetric divisions were decreased, and the expression pattern of the polarity protein Par3, normally present at the apical-lateral membrane of basal cells, was dispersed in the cells. We propose a mechanism in which Notch activation by Jag1 decreases p63 expression at the basal layer, which in turn reduces stratification by decreasing the number of asymmetric divisions and increases differentiation.